Modelling the Monetary Impact of Oil Price Volatility in Nigeria: Evidence from GARCH Models - Chile, Nzeh Innocent; Duru, Innocent.U.; Yusuf, Abubakar; Okafor, Bartholomew .O.N.; Eze, Millicent Adanne (Energy Economics Letters, 2021)
This paper investigated the impact of oil price volatility on some monetary variables in Nigeria under the framework of the GARCH models. The paper utilized three alternative error distributions in order to assist in providing better model fits and thus avoid biased results. Using monthly series over a period of 2006-2019, our findings revealed that, apart from the usual normal error distribution other error distributions perform better in the modelling of the impact of oil price volatility on monetary variables in Nigeria. The findings of the study also revealed that the asymmetric parameters of the models show evidence of leverage effect and oil price volatility plays a significant role in the determination of volatility of monetary variables. We, therefore, recommend that in modelling volatility of oil price and monetary variables in Nigeria, different error distributions should be considered.